1995
DOI: 10.1042/bj3060771
|View full text |Cite
|
Sign up to set email alerts
|

Nitrone spin traps and a nitroxide antioxidant inhibit a common pathway of thymocyte apoptosis

Abstract: Oxidative stress has recently been suggested to be a mediator of apoptotic cell death [Buttke and Sandstrom (1994) Immunology Today 15, 7-10], although evidence that this phenomenon is a widespread component of apoptosis is lacking. When rat thymocytes were exposed to the glucocorticoid methylprednisolone (MPS), a progressive increase in intracellular peroxides and a decrease in glutathione (GSH) were observed to accompany the onset of apoptosis. Using Percoll density gradients to isolate subpopulations of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(95 citation statements)
references
References 54 publications
2
93
0
Order By: Relevance
“…These include the role of elevated GSH in either increasing DNA repair (Kelland, 1993) or increasing the inhibitory effect on apoptosis by buffering an endogenous drug-induced oxidative stress (Chiba et al, 1995;Slater et al, 1995). This is consistent with reports that cells overproducing the Bcl-2 protein have correspondingly higher intracellular GSH levels, which may contribute to the antiapoptotic functions of Bcl-2 (Hockenbery et al, 1993;Chiao et al, 1995).…”
Section: Increased Inactivation By Thiol-containing Moleculessupporting
confidence: 79%
“…These include the role of elevated GSH in either increasing DNA repair (Kelland, 1993) or increasing the inhibitory effect on apoptosis by buffering an endogenous drug-induced oxidative stress (Chiba et al, 1995;Slater et al, 1995). This is consistent with reports that cells overproducing the Bcl-2 protein have correspondingly higher intracellular GSH levels, which may contribute to the antiapoptotic functions of Bcl-2 (Hockenbery et al, 1993;Chiao et al, 1995).…”
Section: Increased Inactivation By Thiol-containing Moleculessupporting
confidence: 79%
“…Studies aimed at establishing the chronology of apoptotic events support an early role for ROS. When apoptotic thymocyte populations are collected using Percoll gradients 13 or identified by flow cytometry, 16 small increases in ROS can be seen shortly after steroid treatment. The evidence of lipid peroxidation seen by Bustamante et al 19 also appeared shortly after drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that in pancreatic cancer cells, treatment with BD caused reduction of intracellular GSH in a does-dependent manner. Glutathione is the most abundant bulk antioxidant, which prevents apoptosis and maintains viability of the cells (Slater et al, 1995). PANC-1 cells deprived of GSH on exposure to BD became more vulnerable to oxidative stress when their ability to scavenge and detoxify the various metabolically generated reactive oxygen intermediates was impaired.…”
Section: Discussionmentioning
confidence: 99%